Energy-Efficient Fruit Dehydration Regimes in Modified Atmosphere - Popescu V.S.; Tsislinscaia N.I.; Vishanu I.V.; Melenchiuc M.G.; Balan M.M.; Vishanu V.V. (Problems of the Regional Energetics, 2024)
The aim of this work is to establish energy-efficient fruit dehydration regimes in a modified atmosphere. To achieve the goal, an experimental electrical installation was developed, which applies in the technological process the CO2 modified atmosphere dehydration method. Carbon dioxide was used as a drying agent because it is harmless for food and for the human body, including even children and is often used in food industry. The researches were focused on the example of the local origin fruits dehydration, but in particular, peaches were selected as the main object of the research, because they are extremely sensitive to both storage and processing, and the current technologies applied in their case have low efficiency due to adverse reactions that cause processing defects. The essential problems in the dehydration of peaches are the oxidation of the superficial layer and the browning, which considerably reduce the quality of the finished products and also require an increased energy intake, and because of the mentioned shortcomings, these fruits are mainly used during the season, being mainly consumed fresh, nevertheless the dried fruits are of interest and are sought after by consumers the year-around. The main results obtained with the application of the elaborated installation are: increasing in the energy efficiency and the quality of the finished products. The significance of these results lies in the solution of the essential characteristic problems of the fruit dehydration process, which are currently faced by specialized companies in the respective field.